(untitled) (Philological Studies, 2019)
The paper deals with the occurrence of multiculturality, interculturality and Otherness in the contemporary Slovenian novels written by the authors Brina Švigelj Mérat, which is also known as Brina Svit, Erica Johnson Debeljak and Goran Vojnović. The novels by Brina Svit, who was born in Slovenia but moved to France, are filled with the protagonist’s sense of alienation and uncertainty due to her (double) identity problems, mutual issues and/or transcultural living in different countries, which is the fact that shows certain autobiographical impact. Likewise, the narrative prose of Erica Johnson Debeljak is based on the autobiographical experiences that are related to author’s migration from America to Slovenia and her later perception of Slovenian language, culture, living style, customs etc. The female author gives a special attention to the Slovenian stereotypical judgment of the American, the Western European and the Yugoslav Otherness. Slovenian underestimation of people from the (southern) Balkan countries has the even more significant role in the novels by Goran Vojnović, who faced the stigmatization himself while living on Fužine, the place that is also known as the Slovenian multicultural “ghetto”. Vojnović’s protagonists are often verbally labeled because of their different origins and/or cultural status; therefore, they fight with their own sense of alienation, identity problems and lack of social communication. In this way, the intercultural aspect of the selected novels is represented in many connected levels: by including words, phrases or statements in foreign languages; by motivicthematic basis, built on the several social-cultural issues (sense of alienation, migrations, conception of double identity, displaced persons, multilingualism etc.); by the intertextual quotations of literary works written by the authors who have also shared their intercultural experience with the audience.